LAW ENFORCEMENT AGAINST FRAUD IS UNDERSTANDING INVESTIGATION BULGING - Nirwana, Muhammad Alfaruq Nirwana (Universitas Duta Bangsa Surakarta, 2022)
ABSTRACT The development of investment at this time has progressed so fast and rapidly. The investment itself in this case can be used by investors by using media applications that utilize technological developments to carry out their activities. In Indonesia, fraudulent investment applications are widespread, which raises the problem that in Indonesia there is no specific regulation related to fraudulent investment actions. This study aims to find out how the law is enforced against fraudulent investment actors and how legal protection efforts are given to victims of fraudulent investments. This research uses normative legal research methods. And please note that fraudulent investment actors in Indonesia can be charged with Article 378 of the Criminal Code concerning Fraud and because they do not have a permit, fraudulent investments can be subject to Article 103 of Law Number 8 of 1995 concerning Capital Markets and related to investment victims in applications because they use electronic media. it may be subject to Article 28 paragraph 1 of Law Number 11 of 2008 concerning Information and Electronic Transactions Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions